From communication to co‐operation: Reconceptualizing social workers' engagement with children. Issue 2 (11th December 2019) - Ruch, Gillian; Winter, Karen; Morrison, Fiona; Hadfield, Mark; Hallett, Sophie; Cree, Viv
Abstract: Communicating and engaging with children is a foundational component of child care social work practice, but all too frequently, in the wake of serious incidents, it is the focus of criticism. Drawing on findings from a large‐scale ESRC‐funded research project conducted in the four U.K. nations, this paper explores, through a psychosocial analytic lens, how social workers anticipate, enact and reflect on their encounters with both children and their families. Close analysis of what social workers said about their practice alongside what they were observed to do in practice revealed perceptions, patterns and processes of communication that, first, minimize emotions and the complexity of the professional task and second, overly privilege verbal interaction. Drawing on Sennett's (2012) ideas this paper offers a reconceptualisation of this professional task, from a communicative to a co‐operative one. It affords and creates a space in which social workers can develop more attuned communicative practices that include rituals, gestures and the minimal use of force. The theoretical insights and evidence‐informed practice recommendations arising from this research have conceptual significance for the social work discipline and practical significance for the child care social work profession, across national and international contexts.